Application of Simulation Packages in Classes of Switching Converters - Rankis, I.; Rodionova, I. (Elektronika ir Elektrotechnika, 2006)
There are presented results of computer simulation of power electronic circuits applying programme package PSIM. Such a simulation is foreseen for teaching of students on subject of learning of switching converters, i.e. converters realized on base of powerful transistors switched with free preset frequency and different algorithms of control. In the first part a DC/DC converters are examined and simulation results compared with ones calculated by formulas describing processes. It is shown that coincidence is very good. The next part is devoted to examining of switching converters with sinus shape output current which are basic for sinus shape PWM technologies. Single phase and three phase schemes are examined and results of simulation are satisfying. As the third part are presented schemes for obtaining a sinus shape of input current of different sorts of line-frequency converters. Presented equations can be applied for teaching of students on subject of power electronics, but application of programming packages allow to virtualized learning process. Il. 12, bibl. 1 (in English; summaries in English, Russian and Lithuanian).